Organizational Change, Skill Formation, Human Capital Measurement: Evidence From Italian Manufacturing Firms - Gilberto Antonelli; Roberto Antonietti; Giovanni Guidetti (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2009)
Basing on a job competition approach, in this paper we provide a labour demand-oriented measure of human capital as defined by the amount of specific skills a firm generates through work-based training (WBT) activities. By merging three rich firm-level datasets, we estimate the impact of a set of variables that are supposed to affect both the propensity to invest in WBT and the intensity of training within the Italian manufacturing industry over the period 2001-2005.The estimates show that the effects of innovation on WBT is higher when the introduction of new technologies is supported by organizational innovations. When looking at the nature of WBT, we investigate the different determinants of the firms' propensity to provide both in-house and outside training. Finally, we estimate training intensity in terms, respectively, of the number of training activities provided, private and total training costs and the share of trainees.
Keywords: 330